2014
DOI: 10.1016/j.whi.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Selected Preconception Health Indicators and Birth Weight Disparities in a National Study

Abstract: Background This analysis explored the effect of timing, sequencing, and change in preconception health across adolescence and young adulthood on racial/ethnic disparities in birth weight in a diverse national cohort of young adult women. Methods Data came from Waves I (1994–1995), III (2001–2002), and IV (2007–2008) of the National Longitudinal Study of Adolescent Health. Eligibility was restricted to all singleton live births to female non-Hispanic White, non-Hispanic Black, Mexican-origin Latina, or Asian/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The association with low birth weight was also suggested in other studies. An analysis of 38 cases of Dandy–Walker malformation identified between 1967 and 1987 by Pascual‐Castroviejo et al [] reported that 34% of the infants with DWM had a birth weight below 3,000 g. In our data, we found that approximately 33% of all liveborn singleton infants with DWM and 35% of isolated cases were born premature (<37 weeks) and approximately 28% of liveborn singleton cases had birth weights below 2,500 g. Because non‐Hispanic black infants are more likely to have low birth weight [Strutz et al, ; Thomas et al, ], we stratified birth weight by maternal race/ethnicity to assess for heterogeneity of effects. In our analysis, the association with non‐Hispanic black race/ethnicity was lower compared to other race/ethnicity categories.…”
Section: Discussionmentioning
confidence: 46%
“…The association with low birth weight was also suggested in other studies. An analysis of 38 cases of Dandy–Walker malformation identified between 1967 and 1987 by Pascual‐Castroviejo et al [] reported that 34% of the infants with DWM had a birth weight below 3,000 g. In our data, we found that approximately 33% of all liveborn singleton infants with DWM and 35% of isolated cases were born premature (<37 weeks) and approximately 28% of liveborn singleton cases had birth weights below 2,500 g. Because non‐Hispanic black infants are more likely to have low birth weight [Strutz et al, ; Thomas et al, ], we stratified birth weight by maternal race/ethnicity to assess for heterogeneity of effects. In our analysis, the association with non‐Hispanic black race/ethnicity was lower compared to other race/ethnicity categories.…”
Section: Discussionmentioning
confidence: 46%
“…Health prior to conception does not explain the racial/ethnic disparity in low birth weight (202). However, chronic stress prior to conception increases the risk of low birth weight (201).…”
Section: History and Etiology Of The Fetal Origins Of Cardiovascular DImentioning
confidence: 99%
“…A total of 19 studies reported the drinking pattern during pregnancy, including the number of alcoholic drinks per day, 27,37,39,42,54 and per week. 20,22,26,33,38,39,44,46,55 The studies included also reported the amount of alcohol (g) consumed monthly, 25,27 and the number of drinking occasions in the previous year.…”
Section: Study Characteristicsmentioning
confidence: 99%